Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi di Kawasan Timur Indonesia (KTI) Periode Tahun 2018-2022 - Syahputra, Muhammad; Fauzi, Reza Nur; W.K, Ardhian Rizki; Quathro T, Audi; Sanjiwo, Dharma; Ardian, Rizki; Ferdiansyah, Kelvin; Zarkasyi, Muhammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the impact of infrastructure such as roads, sanitation, electricity, education, and information technology on economic growth in Eastern Indonesia. Using quantitative methods and panel data analysis, this study found that these infrastructure factors have a significant influence on economic growth. While road and sanitation infrastructure show a positive and significant effect, electricity has a negative and significant impact. Education infrastructure shows no significant effect, and information technology has a positive but insignificant impact on economic growth. This study suggests recommendations for the government to focus on improving electricity infrastructure and ensuring equal access to education and information technology facilities.